Marriage, Law and Polyamory. Rebutting Mononormativity with Sexual Orientation Discourse? - Christian Klesse (Oñati Socio-Legal Series)
This paper traces the genealogy of sexual orientation discourse in US legal scholarship and explores potential drawbacks of the articulation of a sexual orientation argument in the field of relationship recognition. After a long period of refraining from campaigning for legal recognition of multi-partner relationships, polyamory activists have recently shown a stronger interest in litigation. This paper identifies reasons for this shift in recent successes of the campaign for same-sex marriage rights and critically discusses proposals to frame polyamory as a sexual orientation to achieve multi-partner marriage rights through litigation. I argue that advocating a sexual orientation model of polyamory is likely to reduce the complexity and transformative potential of poly intimacies, limit the scope and reach of potential litigation, obstruct the capacity of poly activism to form alliances and increase the likelihood of poly activism to settle for legal solutions (i.e. marriage) that are exclusive and reproductive of a culture of privilege.